Tinjauan Yuridis Penjatuhan Hukuman terhadap Bidan yang Melakukan Tindakan Pidana Aborsi - Abidin, Sanjaya; Gustin, Fiony; Pasaribu, Andre Hakim; Batubara, Sonya Airini (Universitas Medan Area, 2019)
Pregnancy is a very happy situation for every partner who has been legitimate. In connection with this we still often encounter couples who do not value pregnancy so take the decision to do inhumane actions, one of which is abortion. Abortion is a form of criminality that is still very difficult to be handled by the public or the government, this is because there are still gaps for the perpetrators to carry out these actions and the deterrent effect is still lacking for abortion. This study aims to determine the legal arrangements and accountability for abortionists. This study uses normative juridical research methods, to address abortion problems that occur without looking at it from one perspective, but comprehensively. The results showed that the legal arrangements for the crime of abortion have been regulated in the law adjustment for abortion has been regulated ib article 194 law number 36 year 2009, about a midwife who help those who committed abortion is included in criminal code article 349